1993
DOI: 10.1093/ajcn/57.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of body composition in human immunodeficiency virus-infected patients: tetrapolar body impedance analysis indicates significant malnutrition

Abstract: Total body water, body fat, body cell mass (BCM), extracellular mass (ECM), and the ECM-BCM ratio by impedance analysis were determined in 193 human immunodeficiency virus (HIV)-infected patients and 340 control subjects. Walter Reed (WR) classification was WR 2 in 26, WR 3-5 in 85, and WR 6 in 82 patients. Whereas resistance was increased, reactance and the phase angle were significantly reduced in all patient groups. Neither body weight nor body mass index (BMI) was affected in WR 2 patients, but BCM was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(56 citation statements)
references
References 15 publications
3
47
0
4
Order By: Relevance
“…50 kHz unifrequency BIA is the most commonly used BIA method and has been validated in HIV-infected patients (Kotler et al, 1996). Using this method, Ott et al (1993) observed, as in this study, a decrease in lean body mass and an increase in total body water during the early stages of HIV infection. However, 50 kHz unifrequency BIA does not allow intra and extra cellular water to be measured contrary to 5 kHz and 100 kHz bifrequency BIA.…”
Section: Discussionsupporting
confidence: 72%
“…50 kHz unifrequency BIA is the most commonly used BIA method and has been validated in HIV-infected patients (Kotler et al, 1996). Using this method, Ott et al (1993) observed, as in this study, a decrease in lean body mass and an increase in total body water during the early stages of HIV infection. However, 50 kHz unifrequency BIA does not allow intra and extra cellular water to be measured contrary to 5 kHz and 100 kHz bifrequency BIA.…”
Section: Discussionsupporting
confidence: 72%
“…HIV disease is associated with loss of lean (Kotler et al, 1985;Ott et al, 1993) and fat (Mulligan et al, 1997b;Sharpstone et al, 1996) body mass, as a result of opportunistic infections (Paton et al, 1997), metabolic (Melchior et al, 1991;Mulligan et al, 1997a) and hormonal (Strawford & Hellerstein, 1998) changes, decreased food intake and nutrient malabsorption (Kotler, 1998). In women, HIV-related weight loss occurs largely at the expense of body fat (Grinspoon et al, 1997;Kotler et al, 1999), and mean prepregnancy weight of HIV-positive women has been found to be lower than that of HIV-negatives in African settings (Castetbon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Studies done since the beginning of the AIDS epidemic, mostly in industrialised countries, showed the impact of HIV infection on nutritional status from the early stages of HIV infection (Graham et al, 1993;Ott et al, 1993) and its deleterious prognostic signi®cance (Kotler et al, 1989;Guenter et al, 1993). Recently, malnutrition has become much less frequent among HIV-infected subjects in industrialised countries due to the introduction of more effective antiretroviral treatments (Carbonnel et al, 1998), but countries with limited resources such as Burundi barely bene®t from these expensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition among HIV infected patients is mostly related to the development of opportunistic infections (OI) (Graham et al, 1983), tuberculosis (TB) being the most frequent in Africa (Aubry et al, 1992;Colebunders & Latif 1991), Independently of OI, HIV infection is, by itself, a cause of malnutrition, which therefore affects many patients from the early stages of HIV infection (Ott et al, 1993). In addition, malnutrition is an independent cause of immunodepression (Kotler et al 1989), adding its deleterious effects to those of HIV and facilitating the development of OI.…”
Section: Introductionmentioning
confidence: 99%